Ionheart - Kummer, Lukas, 1988- (Top Shelf Productions, 2025)
This head-spinning, time-bending graphic novel is a nuclear fusion of fantasy and science fiction whose every page glows with an eerie light. Will you survive the blast? Pursued by a terrifying demon, a young knight flees across the radioactive ruins of a fairy-tale land. His only weapon is the same cursed power that once destroyed this world-what some would call magic, and others would call technology. As his relentless enemy draws closer, the knight's terrible secrets begin to unfold. How many lives has he lived? Is this the past, the present, or the future? Is he destined to bring love, or unimaginable destruction? And if he fails ... will humanity get another chance?